2019
DOI: 10.1177/1179547619855383
|View full text |Cite
|
Sign up to set email alerts
|

Nutcracker Syndrome Accompanying With Superior Mesenteric Artery Syndrome: A Case Report

Abstract: Purpose: The duodenum and the left renal vein (LRV) occupy the vascular angle made by the superior mesenteric artery (SMA) and the aorta. When the angle becomes too acute, compression of either structure can occur. Although superior mesenteric artery syndrome (SMAS) and renal Nutcracker syndrome (NCS) share the same pathogenesis, concurrent development has rarely been reported. Case report: A 38-year-old female patient with a past history of gastrojejunostomy operated 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…So, one might assume that as a person loses enough weight to cause one of the syndromes, it should not be uncommon to have the second syndrome develop as well. Looking at the literature, we were surprised to find only a few case reports of concomitant SMA and NCS [ 1 , 26 31 ]; this dual presentation is extremely rare, and our case adds importantly to the scant literature available.…”
Section: Discussionmentioning
confidence: 76%
“…So, one might assume that as a person loses enough weight to cause one of the syndromes, it should not be uncommon to have the second syndrome develop as well. Looking at the literature, we were surprised to find only a few case reports of concomitant SMA and NCS [ 1 , 26 31 ]; this dual presentation is extremely rare, and our case adds importantly to the scant literature available.…”
Section: Discussionmentioning
confidence: 76%
“…5 During our research we found nearly 20 additional cases. [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][17] Our patient was the typical thin young female, although SMA syndrome may also occur in men and in all age groups. 1 The diagnosis of SMA syndrome is based on the clinical setting and with the help of imaging modalities such as CT or MRI scans that may show a dilated duodenum proximal to the clamp, a short aortomesenteric distance, or a narrow aortomesenteric angle.…”
Section: Discussionmentioning
confidence: 99%
“…Discusión Los síndromes de arteria mesentérica superior y del cascanueces son infrecuentes, y corresponden a la categoría de los denominados "síndromes vasculares" que reúne a patologías caracterizadas por un pinzamiento anatómico que involucra al menos una estructura vascular. La coexistencia de estos dos síndromes en un mismo paciente ha sido escasamente reportada en la literatura a la fecha, con un total de 13 casos 1,2,3,4,5,6 . Esta coexistencia se explica debido a que ambas condiciones comparten un mecanismo fisiopatológico común: la disminución del espacio comprendido entre la aorta abdominal y arteria mesentérica superior.…”
unclassified